Innate immunity in children - Speert, David (Henry Stewart Talks, 2009)
Host defense in children is composed of non-specific, innate and adaptive limbs, Innate immunity is critical in defense against infection in children, Innate immunity is composed of cellular and humoral elements, Defects in innate immunity provide powerful insights into the importance of this limb of the host defense system in defense against infection, New therapeutic strategies are being developed based upon novel observations of innate immunodeficiencies in children